(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2009)
Insulinomas, the most common of pancreatic endocrine tumors, usually present with neuroglycopenic and adrenergic features. Chronic or long standing recurrent hypogycaemia can produce intellectual deterioration and neuropsychiatric manifestations. Diagnosis of insulinoma relies on clinical features along with laboratory tests and imaging investigations to aid in localization. A 32-year-old male who presented with prominent neuropsychiatric manifestations and received anti-epileptics as a case of epilepsy and was ultimately diagnosed as insulinoma is reported here. The patient experienced fasting hypoglycemia with neuropsychiatric manifestations; computerized tomography (CT scan) and magnetic resonance imaging (MRI) revealed a diffusely enhanced mass in the head area of pancreas which was histopathologically found to be an insulinoma after hand assisted laparoscopic enucleation. Surgical excision is the treatment of choice and is curative in most cases. Key words: Insulinoma; Psychiatric Manifestation. DOI: 10.3329/bsmmuj.v2i1.3710 BSMMU J 2009; 2(1): 39-41